Skip, Search, Speculate - Turning a Frozen LLM into Its Own Lightweight Drafter for Lossless Inference Speedup - Olsson, Hugo (My University)
This thesis has investigated the possibility to speedup inference by producing a self-speculative setup where the original model is verifier and drafter. The model is frozen so the original quality is preserved and no retraining required. The frozen model switches between being verifier and drafter. In the drafter mode, a gap of almost all layers are skipped and an approximated nearest neighbors (ANN) LM-head is used. To prevent completely degraded performance from skipping many layers, this thesis proposes Hidden Vector Casting (HVC) which casts the hidden vector from the geometric representation of the exit-layer to the geometric representation of the entrance-layer. The thesis has produced an open source implementation to train the HVC, build the ANN head and run self-speculative inference with KV-cache handling. It also includes experiments to evaluate what layer-skipping ablations that are the best to skip as many layers as possible while degrading the generation performance as little as possible. The thesis found that skipping an contiguous internal gap of layers is in general advantageous compared to early-exit, late-start of an periodic variant of skipped layers. The selected layer skipping ablations to produce inference systems were (1,1) and (2,2) which means that all layers except the first and the last are skipped or all layers skipped except the two first and two last respectively. The found results are average speedups of 1.21× to 1.63× while having on average 0.9% higher peak memory usage compared to normal inference and producing identical generation to normal inference up to what the selected floating point precision allows for. The speedup depends on the LM model and the type of prompt used. Larger models seem to have higher potential for speedup while smaller models seem to have less overhead to save computation and thus smaller potential for speedup. Since the mechanism fundamentally is to cheaply speculate ahead of the full model, the results also indicate that more concrete prompts get larger speedups while more open-ended prompts produces lower speedups in general. The measured total times to train the HVC and to build the ANN LM-head are 16 to 38 minutes depending on the model. The HVC was trained on a NVIDIA RTX PRO 6000 and the ANN LM-head was built on an Apple MacBook Pro M5 24GB. The thesis uses the models Llama 3.2 1B Instruct, Llama 3.2 3B Instruct, Llama 3.1 8B Instruct, Mistral 7B Instruct 0.3v, and Qwen3 4B. The thesis only investigated smaller models in the range 1–10B parameters due to limitation in computational access. The concept should however work for larger models as well.
Keywords: large language models, self-speculative decoding, inference acceleration, layer skipping, hidden vector casting, approximate nearest-neighbor LM-heads, lossless generation